Практическое клиническое руководство KDIGO по ведению пациентов после трансплантации почки - B. L. Kasiske; M. G. Zeier; J. R. Chapman; J. C. Craig; H. Ekberg; C. A. Garvey; M. D. Green; V. Jha; M. A. Josephson; B. A. Kiberd; H. A. Kreis; M. A. McDonald; et al. (Трансплантология (Москва))
.